Identification of salivary autoantibodies as biomarkers of oral cancer with immunoglobulin A enrichment combined with affinity mass spectrometry - Chu, Hao‐Wei; Chang, Kai‐Ping; Yen, Wei‐Chen; Liu, Hao‐Ping; Chan, Xiu‐Ya; Liu, Chiao‐Rou; Hung, Chu‐Mi; Wu, Chih‐Ching (Proteomics (Weinheim), 2023)
Globally, oral cavity squamous cell carcinoma (OSCC) is one of the most common fatal illnesses. Its high mortality is ascribed to the fact that the disease is often diagnosed at a late stage, which indicates an urgent need for approaches for the early detection of OSCC. The use of salivary autoantibodies (autoAbs) as OSCC biomarkers has numerous advantages such as easy access to saliva samples and efficient detection of autoAbs using well‐established secondary reagents. To improve OSCC screening, we identified OSCC‐associated autoAbs with the enrichment of salivary autoAbs combined with affinity mass spectrometry (MS). The salivary IgA of healthy individuals and OSCC patients was purified with peptide M‐conjugated beads and then applied to immunoprecipitated antigens (Ags) in OSCC cells. Using tandem MS analysis and spectral counting‐based quantitation, the level of 10 Ags increased in the OSCC group compared with the control group. Moreover, salivary levels of autoAbs to the 10 Ags were determined by a multiplexed bead‐based immunoassay. Among them, seven were significantly higher in early‐stage OSCC patients than in healthy individuals. A marker panel consisting of autoAbs to LMAN2, PTGR1, RAB13, and UQCRC2 was further developed to improve the early diagnosis of OSCC.